Donizetti's Lucia di Lammermoor - Cammarano, Salvatore, 1801-1852 (Opera classics library., 2005)
A comprehensive guide to Donizetti's LUCIA DI LAMMERMOOR, featuring insightful and in depth Commentary and Analysis, a complete, newly translated Libretto with Italian/English side-by side, and over 25 music highlight examples.